2015
DOI: 10.1007/s00709-015-0807-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytomixis in the cereal (Gramineae) microsporogenesis

Abstract: The specific features in behavior of the nuclei and chromatin migrating through cytomictic channels as well as in formation of micronuclei in the cereal microsporogenesis have been studied. Immunofluorescence microscopy has allowed for demonstration that the tubulin cytoskeleton does not play a significant role in the intercellular migration of nuclei. Potential involvement of the actin cytoskeleton and SUN-KASH linker complexes in cytomixis is discussed. Comparative analysis of the published and own data sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…& W.C. Greg. (Lavia, Ortiz, Robledo, Fernández, & Seijo, 2011), Triticum and Secale (Sidorchuk, Novikovskaya, & Deineko, 2016), Lippia alba (Mill.) N.E.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…& W.C. Greg. (Lavia, Ortiz, Robledo, Fernández, & Seijo, 2011), Triticum and Secale (Sidorchuk, Novikovskaya, & Deineko, 2016), Lippia alba (Mill.) N.E.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that the mechanism of formation of unreduced gametes by cytomixis is the development of binucleated meiocytes, formed when an entire nucleus migrates to the recipient cell (Sidorchuck et al., 2016; Mursalimov & Deineko, 2018). These nuclei show no signs of damage in the zygo‐pachytene phase and progressively continue meiotic division (Mursalimov & Deineko, 2015), being observable until the nuclear membrane disappears in metaphase I, after which they are undetectable.…”
Section: Resultsmentioning
confidence: 99%
“…Analogous localization of the nucleolus in cytomictic nuclei is evident when considering the cytomictic patterns described in different plant species, such as the cacti of the genus Consolea and various cereal species-wheat, rye, and so on (Negron-Ortiz 2007; Barton et al, 2014;Sidorchuk et al, 2016). However, the authors of the mentioned works did not pay attention to the nonrandom nucleolus localization in the migrating nuclei.…”
Section: Resultsmentioning
confidence: 99%
“…If this function is disturbed or changed, the nucleus may be involved in cell‐to‐cell migration. Other researchers dispute the anchoring function of MTs in cytomixis (Sidorchuk et al, , ), for example, microsporocytes of mutant tobacco lines and wheat‐rye hybrids with partial or complete nuclear loss, there are no visible changes in reticular and radial MT systems were observed, and micronuclei were not active in organizing F‐actin bundles or MTs. In this study the authors suggested that this blockage was due to an absence of MTOCs (MT‐organizing centers) on the surface of micronuclei (Sidorchuk et al, ).…”
Section: Cytoskeleton Functions In Nuclear Migrationmentioning
confidence: 99%